The Preservation of Lampung and Baduy Cultures in Islamic Education Literacy - Syafe’i, Imam; Wasehudin, Wasehudin; Wahyudi, Didik (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2025)
The preservation of Lampung and Baduy cultures within the framework of Islamic education literacy is a crucial effort to safeguard rich cultural heritage in alignment with Islamic values. Both communities possess unique and traditional cultures that reflect a strong worldview and faith rooted in Islam. This study aims to understand how the preservation of Lampung and Baduy cultures can become an integral part of Islamic education and how it can contribute to shaping Islamic character in younger generations. The research employs a descriptive-analytical approach, collecting data through literature review, field observation, and interviews with local community leaders. The findings indicate that preserving the cultures of Lampung and Baduy can be integrated into Islamic education literacy through several key aspects. First, Character Education: Cultural values such as interreligious harmony, honesty, and simplicity can be taught within the context of Islamic education to shape an Islamic character. Second, Environmental Awareness: The Baduy people, for instance, maintain a close relationship with nature. Concepts of sustainability and environmental appreciation can be included in Islamic teachings about human responsibility as stewards (Khalifah) of the Earth. Third, Social Values: Both communities emphasize cooperation, solidarity, and mutual assistance. These can be incorporated into Islamic education to teach social values like zakat and charity (sadaqah). Fourth, Respect for Ancestors: Both groups uphold traditions of honoring their ancestors. In Islamic education, respect for parents and elders aligns with teachings on filial piety and gratitude. Fifth, Local Arts and Culture: Local art forms, such as traditional dances and music, can be integrated into Islamic arts education that values beneficial and morally supportive artistic expressions. Preserving the cultures of Lampung and Baduy within Islamic education literacy is not only about maintaining traditions but also about nurturing a strong Islamic character in the younger generation. By combining these local cultural values with Islamic teachings, education becomes a powerful tool for both cultural preservation and the development of individuals grounded in Islamic principles.